ESG Disclosure dan Implikasinya terhadap ROA, ROE, dan Tobin’s Q: Studi Perusahaan Terdaftar di BEI - Bambang Sukaryono; Tasrim Tasrim (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to test the impact of Environmental, Social, Governance (ESG) disclosure on company performance in the form of ROA, ROE and Tobin's Q values. ESG disclosure encourages companies to adopt business models that have long-term and sustainable benefits. The importance of ESG practices for stakeholders makes the relationship between ESG disclosure and company performance interrelated. The variables used in this study are dependent variables (ESG disclosure), independent variables (ROA, ROE and Tobin's Q). The population in this study is companies listed on the IDX in 2024. Sample collection was carried out by purposive sampling. Based on the purposive sampling method, the sample obtained was 80 companies. The analysis method used in is multiple regression analysis. The findings of this study show that ESG disclosure has no significant effect on ROA, ROE and Tobin's Q.